Impact of The Establishment of Listening Skills on the Quality Level of Customer Complaints Handling Ability (Case Study in Business Communications Course Students Yogyakarta) - Lucia Nurbani Kartika (Publikasi Indonesia, 2022)
Product or service provided by a customer feedback on a product or service. Of the quality of the product or service used by the customer. More and more complaints given by customers require extra attention for every company that receives complaints to improve in the manufacture of products or services. For this reason, every company must be able to provide satisfaction to its customers by one way of responding and handling customer complaints appropriately and correctly. The methodology used to conduct this research is a quantitative approach to establish a causal relationship between the impact of listening skills on the customer's ability to handle complaints. In this case, it is a student case study. Based on the above Based on the research results, communication is certainly the most important key in building good relationships between individuals. Through oral or written communication, it is hoped that the public can fully understand what is conveyed by the sender of the message. Inevitably, communication is the most important thing in determining customer satisfaction of a company. Customer complaints about the use of a product or service provide feedback on the quality of the product or service used by customers. Therefore, the authors initiated “The Effect of Listening Skills Training on the Quality Level of Customer Complaint Management” and achieved significant results.